A very rare vascular complication of the Edwards expandable eSheath during transcatheter aortic valve replacement. Issue 3 (14th January 2023) - Savvoulidis, Panagiotis; Nadir, Adnan M.; Mechery, Anthony; Doshi, Sagar N.
Abstract: Transcatheter aortic valve replacement (TAVR) has revolutionized the management of severe symptomatic aortic valve stenosis. TAVR is now indicated as an alternative to surgical replacement in a wide risk profile ranging from high to low surgical risk. Although vascular complications have decreased in frequency over time, with the introduction of lower profile delivery systems and sheaths, they remain one of the most frequently encountered and serious complications of TAVR. Patient‐specific predisposing factors have been well characterized. However, much less is known about device‐specific complications. Awareness of the possible device‐related complications may lead to earlier identification, prompt management, and better outcomes. We report a previously unreported complication of the Edwards expandable eSheath that lead to avulsion of the external iliac artery following successful TAVR with a 29‐mm Edwards Sapien 3 transcatheter heart valve. Bleeding was promptly controlled with an occlusion balloon and emergency surgical repair was required with a favorable outcome.